Selective insecticide applications directed against Triatoma infestans (Hemiptera: Reduviidae) affected a nontarget secondary vector of chagas disease, Triatoma garciabesi - Rodríguez Planes, Lucía Inés (2016)
The control of nondomiciliated triatomine species adapted to peridomestic habitats represents a challenge because they are connected to sylvatic colonies, and pyrethroid insecticides have limited effects outdoors. The effects of residual insecticide spraying have rarely been assessed on secondary triatomines. Triatoma garciabesi (Carcavallo, Martinez, Cichero, Prosen & Ronderos, 1967) is a nontarget vector that inhabits the dry western Chaco region, and a member of the Triatoma sordida Sta°l 1859 complex. Little is known on the capacity of T. garciabesi to invade and establish viable domestic or peridomestic colonies, and on its response to residual insecticide sprays directed against Triatoma infestans Klug 1834. The presence and abundance of triatomines were assessed by timed manual collections annually or biannually (spring and fall) during 10 yr after a community-wide insecticide spraying campaign and selective insecticide sprays directed against T. infestans in a rural village of northwestern Argentina. T. garciabesi mainly occupied peridomestic habitats associated with chickens, and was unable to colonize human sleeping quarters. Trees with chickens occurred in nearly all houses and were infested in >25% of the occasions. The abundance of bugs at house-compound level was best explained by a generalized estimating equation model that included selective insecticide sprays during the previous semester (negative effects), chicken abundance (positive effects), seasonality, and their interactions. Our results suggest that insecticide applications targeting T. infestans affected the abundance of T. garciabesi, and reduced the likelihood of future infestation.